2019
DOI: 10.3390/su11195166
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Health Risks of Heavy Metals in Farmland Soils of Drinking Water Protection Areas and a Contaminated Paddy Field in Taiwan

Abstract: This study assessed heavy metal contents and their mobility, bioaccessibility, environmental risk, and health effects in the farmland soils of Drinking Water Source Quality Protection (DWSQP) areas contaminated by livestock manure and a paddy field contaminated by co-use of irrigation and drainage canals in Taiwan. The risk assessment code (RAC) and synthesis toxicity index (STI) for the soils were obtained. The potential health effects caused from soil direct ingestion by hand-to-mouth activity and dermal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…It showed that the average population life time cancer risk associated with crustaceans and tilapia consumption (0.007–0.012) and ingestion of SW and GW (1.423 × 10 −7 –2.607 × 10 −2 ) would result to approximately 1 case per 100,000 population. As per the U.S. Environmental Protection Agency [ 16 ], the value of 10 −5 is an acceptable lifetime carcinogenic risk. However, it should be noted that the PER of the island for metals in crustaceans and tilapia was high.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It showed that the average population life time cancer risk associated with crustaceans and tilapia consumption (0.007–0.012) and ingestion of SW and GW (1.423 × 10 −7 –2.607 × 10 −2 ) would result to approximately 1 case per 100,000 population. As per the U.S. Environmental Protection Agency [ 16 ], the value of 10 −5 is an acceptable lifetime carcinogenic risk. However, it should be noted that the PER of the island for metals in crustaceans and tilapia was high.…”
Section: Resultsmentioning
confidence: 99%
“…Long-term exposure to crustaceans, tilapia, and inland water in Marinduque may result to one cancer patient per 100,000 population, which according to USEPA [ 16 ] is acceptable. Crustaceans, tilapia, and inland water were only the three edible items in Marinduque considered in the calculation of cancer risk probability in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sources of TMs in canal irrigation systems include the transport of irrigation water and sediment in each square meter. The annual runoff volume, QR (m 3 /m 2 /year), can be calculated from the field water balance expressed as QR = QI + QP − ET − QL (5) where QI (m 3 /m 2 /year) is irrigation, QP (m 3 /m 2 /year) is precipitation, ET (m 3 /m 2 /year) is evapotranspiration, and QL (m 3 /m 2 /year) is percolation within each unit area per year. In addition, the different mass transportation paths can be expressed as the following equations, respectively:…”
Section: Estimation Of Tms From Irrigation Watermentioning
confidence: 99%
“…Due to the low mobility of TMs in a soil environment [3], they are not easily diffused or diluted, so they easily accumulate in surface soil. Soil contaminated with TMs in agricultural areas is likely to affect people's health and safety once the TMs have translocated into the edible parts of crops [4,5]. TMs also affect the growth and quality of crops [6].…”
Section: Introductionmentioning
confidence: 99%